Synthesis of Novel BTPhen-Functionalized Silica-Coated Magnetic Nanoparticles for Separating Trivalent Actinides and Lanthanides - Afsar, Ashfaq; Cowell, Joseph; Distler, Petr; Harwood, Laurence M.; John, Jan; Westwood, James (Synlett, 2017)
Bis-(1,2,4-triazin-3-yl)-1,10-phenanthroline (BTPhen) functionalized magnetic nanoparticles (MNPs), which selectively extract Am(III) over europium(III) from 0.1 M HNO3 with fast kinetics and a separation factor of 30 have been synthesized. These MNPs also show a small but significant selectivity for Am(III) over Cm(III) with a separation factor of around 3 in 0.1 M HNO3. We report also the synthesis of these BTPhen and related ligands via an improved synthetic route bypassing the problematic benzylic oxidation with stoichiometric SeO2.
Keywords: spent nuclear fuel; BTPhen ligand; magnetic nanoparticles; solid-phase extraction; benzylic halogenation